Attitudes about Family Medicine among brazilian medical students - Joshua Freeman; Patricia Kelly; Pablo González Blasco; Marcelo Levites (O Mundo da Saúde)
Background and Objectives: As the largest country in Latin America, Brazil’s health care and health education systems have importance beyond its borders. While Family Medicine has not been part of the curriculum in Brazilian medical schools, the health system is built around the “Family Health Program”. Methods: Students attending lectures at 6 São Paulo area medical schools responded to two questions asking what they found interesting about and what the challenges were to Family Medicine in Brazil. 167 responses were coded and sorted using qualitative analysis techniques. Results: Positive aspects of Family Medicine identified were the character of the doctor-patient relationship, the character of the practice, and the philosophy and values of Family Medicine. Obstacles included the lack of knowledge by patients of Family Medicine, the perceived lack of specialty status, and its absence in the medical school and residency structure. Conclusions: The respondents placed greater emphasis on the humanistic and relationship characteristics of Family Medicine, and less on the medical content. This information should be useful to Brazilian Family Medicine educators, and may suggest that efforts to increase student interest in the US consider greater emphasis on these aspects of the discipline.